Studies On The Mechanisms Of Antihyperuricemic Activity, Chornic Toxicity And Formulation Of Phyllanthus Niruri Lignans For The Development Of Potential Antihyperuricemic Agents - Lam, Chan Kit; Hussin, Abas; Abdul Karim Khan, Nurzalina; Murugaiyah, Vikneswaran; Qiu, Ma Hai
In-situ polymerization technique was used to prepare epoxy/organo-montmorillonite (OMMT) nanocomposites by three different mixing sequence methods. The mechanical and morphological properties of epoxy/ OMMT nanocompositeE were studied by flexural tests, fracture toughness (SENB), Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The flexural modulus of epoxy was improved significantly by the incorporation of OMMT. This is attributed to the reinforcement and exfoliation/intercalation of the OMMT. The XRD results showed the formation of exfoliated structure in the epoxy/OMMT nanocomposites. Sequence of mixing influenced the dispersion and intercalation/exfoliation of the OMMT in the epoxy matrix. Appropriate mixing sequence should be selected in order to achieve better exfoliation of OMMT and higher flexural modulus and strength of the epoxy nanaocomposites. In this study, computer aided statistical methods of experimental design (Response Surface Methodology, RSM) was used to investigate the process variables on the flexural properties of epoxy/OMMT nanocomposites. Speed of mechanical stirrer, post-curing time and post-curing temperature were chosen as process variables in the design experimental. Results showed that the speed of mechanical stirrer post-curing time and post-curing temperature were able to influence the flexural modulus and flexural yield stress of epoxy/OMMT nanocomposites.